2021
DOI: 10.1001/jamanetworkopen.2021.26107
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Physician Compensation by Gender in Ontario, Canada

Abstract: Key Points Question Do male and female physicians in Ontario, Canada, receive equal payments for equal work? Findings In this cross-sectional study including 31 481 physicians (nearly all physicians in Ontario), women earned 32.8% less than men annually and 22.5% less daily. After controlling for observable factors associated with earnings, such as practice characteristics, geography (degree of rurality), and specialty, the daily pay gap remained significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…J o u r n a l P r e -p r o o f physicians earn 43.5% less annually than their men counterparts [14].…”
Section: Discussionmentioning
confidence: 96%
“…J o u r n a l P r e -p r o o f physicians earn 43.5% less annually than their men counterparts [14].…”
Section: Discussionmentioning
confidence: 96%
“…Such areas could include moving compensation structures away from piece-work models (eg, FFS), as the literature theorises that such models incentivise higher workloads, 20 as well as addressing the gender pay gap, which has been documented among Ontario physicians. 21 Research exploring the relationship between the gender pay gap and burnout among physicians is lacking, but a 2016 study of 22 581 US adults found that women were significantly more likely to experience depression and anxiety when they were paid less than their equally qualified male counterparts, including among the subset of high-income women. 22 Interventions to increase work-life balance include organisational policy changes to normalise flexible work arrangements such as part-time work or job sharing (ie, two part-time physicians sharing a full-time position), 23 24 as well as exploring innovative strategies such as a time banking programme, where credits are given to participants for time spent on unpaid or under-recognised responsibilities-such as providing last minute clinical coverage or mentoring-and can be redeemed for home or work support services, including meal delivery or grant writing.…”
Section: Discussionmentioning
confidence: 99%
“…Research specifically evaluating the impacts of various compensation policy changes on burnout is needed. Such areas could include moving compensation structures away from piece-work models (eg, FFS), as the literature theorises that such models incentivise higher workloads,20 as well as addressing the gender pay gap, which has been documented among Ontario physicians 21. Research exploring the relationship between the gender pay gap and burnout among physicians is lacking, but a 2016 study of 22 581 US adults found that women were significantly more likely to experience depression and anxiety when they were paid less than their equally qualified male counterparts, including among the subset of high-income women 22…”
Section: Discussionmentioning
confidence: 99%
“…While these data reflect the state of affairs in the United States, this is not a uniquely American problem. Indeed, such a disparity has been seen across the globe [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%